The Impact of Frailty on Changes in Physical Function and Disease Activity Among Adults With Rheumatoid Arthritis. Issue 6 (28th July 2019) - Andrews, James S.; Trupin, Laura; Wysham, Katherine D.; Hough, Catherine L.; Yelin, Edward H.; Katz, Patricia P.
Abstract : Objective: Reduced physical function and frailty are common in rheumatoid arthritis (RA). However, relationships between frailty and changes in physical function and disease activity over time in RA are unknown. We tested whether frailty is a risk factor for worsening patient‐reported physical function and disease activity in RA. Methods: Adults from a longitudinal RA cohort (N = 124) participated. By using an established frailty definition, individuals with three or more of the following deficits were considered frail: 1) body mass index less than or equal to 18.5, 2) low grip strength, 3) severe fatigue, 4) slow 4‐m walking speed, and 5) low physical activity. Individuals with one to two or zero deficits were considered "pre‐frail" or "robust, " respectively. Physical function and RA disease activity were assessed by the Health Assessment Questionnaire (HAQ) and Rheumatoid Arthritis Disease Activity Index (RADAI), respectively, at baseline and follow‐up 2 years later. Regression analyses modeled associations of frailty status with change in HAQ and RADAI scores between baseline and follow‐up with and without controlling for covariates. Associations of individual frailty components with change in HAQ and RADAI scores were also examined. Results: Among adults with RA, baseline frailty status predicted significant increases, or worsening, in HAQ ( β : 0.4; 95% confidence interval: 0.1‐0.8; P < 0.01) but not RADAI scores ( β : 0.5; 95% confidence interval: −0.4 to 1.5; P > 0.05) between baseline and follow‐up in fully adjusted models. Fatigue was an important contributor to this effect. Conclusion: Frailty may be an important risk factor for reduced physical function over time in RA. Future studies should address whether interventions to reduce frailty improve physical function in RA.